Divergent immunity and energetic programs in the gills of migratory and resident Oncorhynchus mykiss. Issue 8 (5th April 2014) - Sutherland, Ben J. G.; Hanson, Kyle C.; Jantzen, Johanna R.; Koop, Ben F.; Smith, Christian T.
Abstract Divergent life history strategies occur in steelhead or rainbow trout Oncorhynchus mykiss, and many populations produce both migrant (anadromous fish that move to the ocean after rearing) and resident (do not migrate and remain in fresh water) individuals. Mechanisms leading to each type are only partially understood; while the general tendency of a population is heritable, individual tendency may be plastic, influenced by local environment. Steelhead hatchery programmes aim to mitigate losses in wild stocks by producing trout that will migrate to the ocean and not compete with wild trout for limited freshwater resources. To increase our understanding of gill function in these migratory or resident phenotypes, here we compare gill transcriptome profiles of hatchery‐released fish either at the release site (residents) or five river kilometres downstream while still in full fresh water (migrants). To test whether any of these genes can be used as predictive markers for smoltification, we compared these genes between migrant‐like and undifferentiated trout while still in the hatchery in a common environment (prerelease). Results confirmed the gradual process of smoltification, and the importance of energetics, gill remodelling and ion transport capacity for migrants. Additionally, residents overexpressed transcripts involved in antiviral defences, potentially for immune surveillance via dendritic cells in the gills. The best smoltification marker candidate was protein s100a4, expression of which was highly correlated with Na+, K+ ATPase (NKA) activity and smolt‐like morphology in pre‐ and postrelease trout gills.